An essay on the tribe Xylographellini (Coleoptera: Tenebrionoidea: Ciidae) - Lopes-Andrade, Cristiano (Zootaxa, 2008)
The tribe Xylographellini is redefined and three genera are formally transferred to it: Scolytocis Blair, to the subtribe Xylographellina; Syncosmetus Sharp and Tropicis Scott, to the subtribe Syncosmetina subtr. nov. The genus Scolytocis is redescribed and diagnoses are provided for the other genera of the tribe. Twenty new species are described: Xylographella speciosa sp. nov.; Scol. bouchardi sp. nov.; Scol. cariborum sp. nov.; Scol. danielssoni sp. nov.; Scol. difficillimus sp. nov.; Scol. fritzplaumanni sp. nov.; Scol. furieriae sp. nov.; Scol. howdeni sp. nov.; Scol. indecisus sp. nov.; Scol. kiskeyensis sp. nov.; Scol. lawrencei sp. nov.; Scol. malayanus sp. nov.; Scol. novaezelandiae sp. nov.; Scol. panamensis sp. nov.; Scol. paschoali sp. nov.; Scol. philippinensis sp. nov.; Scol. thayerae sp. nov.; Scol. werneri sp. nov.; Scol. zimmermani sp. nov.; and Trop. cuccodoroi sp. nov. A key to the subtribes and genera of Xylographellini is provided, as well as keys to the species of Scolytocis, Syncosmetus, Tropicis and Xylographella Miyatake. The taxonomic limits and geographic distribution of the tribe, its subtribes and genera are discussed in light of the new data provided here. The morphological similarities between Xylographellini and Orophiini are briefly discussed.